Muddle school - Whamond, Dave (Kids Can Press, 2021)
"Middle school is tough for Dave. He spends most of his time drawing and living in his own imaginative world. And he's terrified that his classmates will find out and think he's even weirder than they do already. But an extraordinary thing happens when Dave and his friend build a time machine for their science project. Dave travels back to the first day of school (or so he thinks) and is given the opportunity to do a complete reset. Can he do everything over again -- this time in the way he wishes he'd done the first time -- and erase all the embarrassing moments of the last few months? Could he actually become really and truly ... cool?"--